Oral patho dot com : short question and answers on oral and maxillofacial pathology - Kumar Purkait, Swapan (New Delhi : Jaypee, 2014)
Oral Patho Dot Com will hopefully be a very helpful book for the students; as it is entirely a book on "short questions and answers on the subject of Oral Pathology and Microbiology". This book will help the student to understand which questions are more important from which chapter from the vast syllabus and not only that, they will also get the readymade answers for every question from every chapter. Moreover, sincere efforts have been made here to highlight the important topics from different chapters so that the students feel no difficulty in facing the examinations.
1. Developmental Anomalies of Oral and Paraoral Structures 2. Benign and Malignant Tumors of the Oral Cavity 3. Oral Precancerous Lesions and Conditions 4. Diseases of Salivary Glands 5. Odontogenic Neoplasms 6. Cysts of the Oral Region 7. Regressive Alterations of Teeth 8. Bacterial, Viral, and Fungal Infections in Mouth 9. Dental Caries 10. Diseases of Pulp and Periapical Tissues 11. Spread of Oral Infections 12. Physical and Chemical Injuries of Oral Tissues 13. Biopsy and Healing of Oral Wounds 14. Oral Aspects of Metabolic Disorders 15. Diseases of Bone 16. Diseases of Temporomandibular Joint 17. Oral Aspects of Hematological Disorders 18. Periodontal Diseases 19. Oral Aspects of Dermatological Disorders 20. Diseases of Nerves and Muscles 21. Oral Manifestations of Generalized Diseases 22. Syndromes Related to Oral Diseases
Incluye contenido
Keywords: ORAL PATHOLOGY; MAXILLOFACIAL PATHOLOGY